2003
DOI: 10.1074/jbc.m302337200
|View full text |Cite
|
Sign up to set email alerts
|

Effective Association of Kv Channel-interacting Proteins with Kv4 Channel Is Mediated with Their Unique Core Peptide

Abstract: Kv channel-interacting proteins (KChIPs) and neuronal calcium sensor-1 (NCS-1) have been shown to interact with Kv4 channel ␣-subunits to regulate the expression and/or gating of these channels. Here we examine the specificity and sites of these proteins for interaction with Kv channel proteins. Immunoprecipitation and green fluorescent protein imaging show that KChIPs (but not NCS-1) effectively bind to Kv4.3 protein and localize at the plasma membrane when channel proteins are coexpressed. Analysis with chim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…We crystallized a complex of the rat Kv4.3 (also called Kcnd3) N-terminal cytoplasmic domain (residues 1-143) and human KChIP1 (also called KCNIP1; residues 37-216) containing the conserved, functional KChIP core 24 . Initial crystals diffracted poorly and could not be improved.…”
Section: Results the Kchip1-kv43 N-terminal Cytoplasmic Domain Complexmentioning
confidence: 99%
“…We crystallized a complex of the rat Kv4.3 (also called Kcnd3) N-terminal cytoplasmic domain (residues 1-143) and human KChIP1 (also called KCNIP1; residues 37-216) containing the conserved, functional KChIP core 24 . Initial crystals diffracted poorly and could not be improved.…”
Section: Results the Kchip1-kv43 N-terminal Cytoplasmic Domain Complexmentioning
confidence: 99%
“…current densities of silenced channels in CON and AP CHO cells revealed by the change in current induced by reversal of MTSET block with DTT. Currents were evoked with a voltage step to þ 5 mV from À70 mV and represent the pre-existing channels; values were determined by subtracting the pre-DTT current amplitudes from the total, post-DTT responses (n ¼ 9; *Po0.05) (myc-Kv2.1 14 ) were isolated following biotinylation and assayed by immunoblot. Consistent with our electrophysiological data, induction of apoptosis nearly doubled the biotinylated fraction of myc-Kv2.1 without any change in total channel protein ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal KIS domain of KChIP4a, which also harbors an ER retention motif, is made responsible for these trafficking and gating effects [15,81]. In the KChIP4a splice variant the hydrophobic groove, which represents a binding domain of KChIPs for the Kv4 N-terminal helix [30,75,82], can be occupied by its own N-terminal helix in vitro (Figure 2(c)), and it was suggested that it may have to be competed out by the Kv4 N-terminus to allow Kv4/KChIP4a complex formation [83,84]. With KChIP2x and KChIP3x (= KChIP3b) Jerng and Pfaffinger [85] have identified two brain KChIP isoforms, which, like KChIP4a, contain an N-terminal KIS domain.…”
Section: Ca2+ Dependence Of Kv4/kchip Complex Formation and Membrane mentioning
confidence: 99%